2022
DOI: 10.3390/children9060771
|View full text |Cite
|
Sign up to set email alerts
|

Teeth Eruption Disorders: A Critical Review

Abstract: Dental eruption refers to the vertical displacement of a tooth from its initial non-functional towards its functional position. Tooth eruption disorders may be expressed in various clinical conditions, which may be grouped as “primary retention” and “secondary retention”. The purpose of this article is to review the literature and the clinical parameters of the various conditions related to tooth eruption disorders. Materials and Methods: The search strategy of this critical review included keywords in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
1
18
0
3
Order By: Relevance
“…In addition, the teeth could exhibit delayed eruption or impaction. It was reported that the eruption disorders observed in such patients could be the result of structural dental anomalies [13]. It is therefore conceivable that a disorder occurring during enamel formation, which is a part of dental development, could cause variations in the eruption times of children with MIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the teeth could exhibit delayed eruption or impaction. It was reported that the eruption disorders observed in such patients could be the result of structural dental anomalies [13]. It is therefore conceivable that a disorder occurring during enamel formation, which is a part of dental development, could cause variations in the eruption times of children with MIH.…”
Section: Discussionmentioning
confidence: 99%
“…In the comparison of the eruption ages of the permanent teeth of the children in the study and control groups, tooth eruption was assumed to have occurred if any part of the crown was visible on the oral mucosa (Codes 1, 2, and 3). For each participant in the study and control groups, the eruption ages of teeth 11,12,13,14,15,16,17,21,22,23,24,25,26,27,31,32,33,34,35,36,37,41,42,43,44,45,46 and 47 were recorded. The mean age of dental eruption in the children in the study group was compared with that of the control group.…”
Section: Code 3: the Tooth Is In Occlusionmentioning
confidence: 99%
“…Po raz pierwszy schorzenie to zostało opisane przez Proffita i Vig w 1981 r. [5]. Określono, że średni wiek pacjenta z PFE wynosi 13.65 lat [6] z stosunkiem mężczyzn do kobiet 1:2.25 [2]. PFE częściej występuje w tylnym odcinku łuku zębowego i dotyczy przedtrzonowców i trzonowców [7], a z wyłączeniem trzecich trzonowców najczęściej dotyczy pierwszego i drugiego trzonowca we wszystkich czterech kwadrantach jamy ustnej [6].…”
Section: Epidemiologiaunclassified
“…Określono, że średni wiek pacjenta z PFE wynosi 13.65 lat [6] z stosunkiem mężczyzn do kobiet 1:2.25 [2]. PFE częściej występuje w tylnym odcinku łuku zębowego i dotyczy przedtrzonowców i trzonowców [7], a z wyłączeniem trzecich trzonowców najczęściej dotyczy pierwszego i drugiego trzonowca we wszystkich czterech kwadrantach jamy ustnej [6]. PFE dotyka zarówno mlecznych jak i stałych zębów, które mogą wyrznąć się do pewnego momentu a następnie zatrzymać proces wyrzynania, a 84.1% pacjentów cechujących się PFE wykazało rodzinne występowanie [7].…”
Section: Epidemiologiaunclassified
“…Dental eruption is a physiological process at the end of which the erupting tooth will occupy its functional place on the dental arch and occlude with the opposing tooth. The process of tooth eruption can be negatively influenced by a variety of factors [ 1 ]. One of the issues that can arise in the process of dental eruption is ectopic eruption, a pathological situation in which the tooth does not follow its normal eruption path [ 2 ].…”
Section: Introductionmentioning
confidence: 99%